The Role of Anti-interleukin-4 in BALB/c Mice Infected with Visceral Leishmaniasis - Manahel H. Mjefy1 , Altamemy A. K. Aakool2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Leishmaniasis is endemic in Iraq with the visceral form of the disease, caused by the L. donovani complex,is principally endemic in the central part of the country. 45 mice (male) were divided into three groups,the first was injected with (3x106) promastigote as control positive, the second was injected with (3x106)promastigote and treated with anti-interleukin 4 and the third was injected with PBS as control negative.After 30, 45 and 60 days the serum was taken and examined by the ELISA test to find out the level ofinterferon gamma (IFN-?).The present study revealed that the level of (IFN-?) at day 30, was higher in group 2 (539.45±2.352), than ingroup 1 (173.26±1.21), and group 3 (109.69 ± 0.25). At day 45, the level recorded in group 2 (393.89±2.012),than group 1 (286.6±1.521), and group 3 (109.93±0.22). At day 60, the level was in group 2 (259.48±1.841),than group 1 (310.22±1.632), and group 3 (109.69±0.23). The aim of present study was to determine theefficient role of anti IL-4 on IFN-? activity in mice infected with L. donovani. We concluded our results thatthe level of interferon gamma (IFN-?) was higher in group 2 at all periods.